EFEKTIVITAS APLIKASI e-PBB P2 (ELEKTRONIK PAJAK BUMI DAN BANGUNAN PERKOTAAN PERDESAAN) DALAM PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN TANAH BUMBU - Muhammad Rusli; Dwianto Muhammad Latif (Universitas Lambung Mangkurat, 2020)
The Rural Urban Land and Building Tax Electronic Application or e-PBB P2 is an application to simplify the tax payment process for Rural Urban Land and Building Taxpayers. This was implemented by the Tanah Bumbu Regency government in 2019. This study was to find out how effective the UN-P2 application was to increase Tanah Bumbu Regency's PAD. After the implementation of the P2 e-PBB application, the effectiveness of P2 PBB revenue has increased from the previous year. But for its effectiveness it is still declared less effective. However, the presence of P2 PBB revenue also makes the effectiveness of Tanah Bumbu Regency's Original Revenues increase.